The Knowledge and Prevention Treatment of Osteoporosis on Elderly: A Cross Sectional Study - Ezalina, Ezalina; Risma Mardayani; Deswinda; Rina Herniyanti (International Journal of Public Health Excellence (IJPHE), 2023)
According to the World Health Organization osteoporosis is the second ranked, after heart disease. In the worldwide there are 200 million people with osteoporosis. One cause the osteoporosis is the low public knowledge in preventing osteoporosis. This study aims to determine the relationship of knowledge with osteoporosis prevention to the elderly. Cross sectional research design, with total sample of 84 elderly through the Accidental Sampling technique. The sample size was 84 respondents. The research instrument used the OKAT (Osteoporosis Knowledge Assessment Tool) questionnaire as the knowledge of osteoporosis and osteoporosis prevention measures questionnaire. The data analysis used univariate analysis and bivariate analysis . The results of this study found that the knowledge of the elderly was in high category of 60.7% and the prevention of osteoporosis was in good category of 53.6%. The results of statistical tests obtained p 0.02< 0.05, that Ho was rejected, so it can be concluded that there is a relationship between knowledge and osteoposition prevention measures in elderly. Research recommendations require further research by examining factors that have not been studied to explain the phenomenon and describe the condition of osteoporosis prevention comprehensively.